Case report and review of literature: Isolated intramedullary spinal neurocysticercosis - Andino, Diana; Tsiang, John T.; Pecoraro, Nathan C.; Jani, Ronak; Iordanou, Jordan C.; Zakaria, Jehad; Borys, Ewa; Pasquale, David D.; Nockels, Russ P.; Schneck, Michael J. (Frontiers in Neurology, 2022)
Background Cases of isolated intramedullary spinal neurocysticercosis are extremely rare. Only 25 cases have been reported before 2022. Due to its rarity, the diagnosis of spinal neurocysticercosis may be missed. Case presentation We describe a 37-year-old female patient who developed back pain and lower extremity weakness and was found to have an intramedullary thoracic spine cystic lesion. She was taken to the operating room for resection of the lesion. Pathology revealed a larval cyst wall consistent with neurocysticercosis. The patient was started on albendazole and dexamethasone. Her exam improved post-operatively, and she was able to ambulate with minimal difficulty at the time of follow up. Conclusion The case provides insights on the diagnosis and treatment of isolated intramedullary spinal neurocysticercosis. Review of the literature suggests that combined surgical and medical intervention results in significant improvement in the patient's neurological exam, and decreases morbidity associated with the disease. We propose a treatment paradigm for this rare manifestation of neurocysticercosis.